HUBUNGAN TRANSPIRASI DENGAN HASIL DAN RENDEMEN MINYAK BIJI JARAK PAGAR (Jatropha curcas L.) - Bora, Charles Y; Sulistyono, E; Yahya, S; Mahmud, Z (BERITA BIOLOGI, 2008)
The objective of this research was to evaluate the relationship between transpiration, yield and seed oil content of jatropha/jarak pagar (Jatropha curcas L.). The research was conducted at Cikabayan Research Garden of IPB July 2007-July 2008.The experimental design was Randomized Block Design with two factors and three replications. The first factor was genotype of Jatropha: IP-1A, IP-1M and IP-IP. The second factor was irrigation frequency: 7, 14, 21 and 28 days.The observed variables were evapotranspiration and yield component.The results show that the irrigation frequency of 7 days gave a higher evapotranspiration and transpiration rate than 14, 21 and 28 days irrigation frequencies. The differences affected yield component of each genotipe. The interaction effects between genotype and irrigation frequency were fruit number per plant. The transpiration positively and strongly related to fruits number, seed productions and oil production. Increased transpiration was followed by increasing on fruit number 0.014 (0.112 fruits/1/plant) for IP-1A and 0.024 (0.183 fruits/1/plant) for IP-IP; and increasing by 0.029 g (0.23 g/1/plant) for IP-1A and 0.024 g (0.19 g/1/plant) for IP-IP in seed productions. The transpiration correlated to oil production but not to oil content. Each mm of transpiration increased the oil production 0.0094 g (0.075 g/1/plant) for IP-1A and 0.0073 g (0.058 g/1/plant) for IP-IP. Water use of IP-IP genotype was more efficient than IP-1A in fruits number, but the IP-1A genotype more efficient in seed and oil productions. The differences on growth and yield responses of the jatropha genotypes to transpiration can be used as the model to describe the relationship between transpiration and growth and yield of the plant.